Moves Analysis on Abstracts Written by the Students in Academic Writing Class - Ajeng Setyorini (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2017)
This paper contains analysis results on abstracts written by students in Academic Writing course. The analysis includes analyses on moves and linguistic features. The analysis aims at finding out how the abstract writing structures of the English Education students are in the Academic Writing course. The abstract analysis also includes the analysis on the use of the linguistic features in the abstracts. The analysis uses a qualitative research approach. There are totally 10 abstracts that are analyzed. These are then called as the data. Data obtained is analyzed using genre analysis approach. Results of analysis on the 10 abstracts showed that some of the abstracts are written using 5 kinds of moves. All of the abstracts are found using Purpose Move and Method Move. Meanwhile, Situation Move is found in 5 abstracts. 8 abstracts are identified using Result Move. Conclusion Move is found in 5 abstracts. The results also show that all of the abstract writers use pronouns ‘the writer’ and ‘the researcher’. The use of personal pronoun ‘she’ is also found in 1 abstract. Hedges used in abstracts written by students in Academic Writing course vary from modal auxiliary verbs, adjectival, adverbial, nominal to Approximates of degree.